Co-Ultramicronized Palmitoylethanolamide/Luteolin Promotes Neuronal Regeneration after Spinal Cord Injury - Crupi, Rosalia; Impellizzeri, Daniela; Bruschetta, Giuseppe; Cordaro, Marika; Paterniti, Irene; Siracusa, Rosalba; Cuzzocrea, Salvatore; Esposito, Emanuela (Frontiers in Pharmacology, 2016)
Spinal cord injury (SCI) stimulates activation of astrocytes and infiltration of immune cells at the lesion site; however, the mechanism that promotes the birth of new neurons is still under debate. Neuronal regeneration is restricted after spinal cord injury, but can be stimulated by experimental intervention. Previously we demonstrated that treatment co-ultramicronized palmitoylethanolamide and luteolin, namely co-ultraPEALut, reduced inflammation. The present study was designed to explore the neuroregenerative properties of co-ultra PEALut in an estabished murine model of SCI. A vascular clip was applied to the spinal cord dura at T5 to T8 to provoke injury. Mice were treated with co-ultraPEALut (1 mg/kg, intraperitoneally) daily for 72 h after SCI. Co-ultraPEALut increased the numbers of both bromodeoxyuridine-positive nuclei and doublecortin-immunoreactive cells in the spinal cord of injured mice. To correlate neuronal development with synaptic plasticity a Golgi method was employed to analyze dendritic spine density. Co-ultraPEALut administration stimulated expression of the neurotrophic factors brain-derived neurotrophic factor, glial cell-derived neurotrophic factor, nerve growth factor and neurotrophin-3. These findings show a prominent effect of co-ultraPEALut administration in the management of survival and differentiation of new neurons and spine maturation, and may represent a therapeutic treatment for spinal cord and other traumatic diseases.